Iconography analysis of ornaments present under yoni spout at Watu Genuk Site, Kragilan, Mojosongo, Boyolali: Analisis ikonografi ragam hias di bawah cerat yoni di Situs Watu Genuk, Kragilan, Mojosongo, Boyolali - Muhammad Faiz (Berkala Arkeologi, 2021)
Yoni at the Watu Genuk Site, Kragilan, Mojosongo, Boyolali is one of the many Hindu-Buddhist remains of the Ancient Java period found in Central Java. The yoni has ornaments located under the water spout in the form of anthropomorphic beaked figure, turtle, and snakes. This article discusses the meaning of yoni ornaments at the Watu Genuk Site through iconographic and comparative analysis with similar figures. The analysis results show that ornaments under the yoni water spout at the Watu Genuk Site is not only decorative, but also has meaning of representing Hindu mythology in Ādiparwa manuscripts such as Samudramanthana and Garudeya.